Pengaruh Pemberian Reward terhadap Motivasi Belajar Siswa pada Pembelajaran PJOK di SMK PGRI 3 Kediri - Prastyo, Titto Dwi; Hartoto, Setiyo (SPRINTER: Jurnal Ilmu Olahraga, 2025)
Motivation is a crucial factor that needs to be considered in learning, especially in subjects such as PJOK. Motivation plays an important role in determining success in learning. This study aims to determine whether there is an influence of the influence of giving rewards on increasing student learning motivation in PJOK learning at SMK PGRI 3 Kediri, and the population studied is all students of SMK PGRI 3 Kediri. The sample was taken using a random sampling technique so that 27 students were obtained. The research instrument used a pre-test and post-test questionnaire with a student learning motivation questionnaire and a reward questionnaire, to measure the level of influence of giving rewards on increasing student learning motivation. Data analysis was carried out using SPSS version 27, to test the paired t-test to determine whether there is an influence of giving rewards on student learning motivation. The results show a significance value of T count > T table, namely 6950 > 1705 on the student learning motivation questionnaire, and on the reward giving questionnaire, T count > T table, namely 8703 > 1705. And the Sig. value (2-tailed) on all test questionnaires is 0.001. It was stated that there was a significant influence on giving rewards on students’ learning motivation in PJOK learning at SMK PGRI 3 Kediri.